PERAN USAHA MIKRO, KECIL DAN MENENGAH (UMKM) DALAM PENGEMBANGAN EKONOMI INDONESIA - Delia Torsa Purba; Wafiyah Ningrum; Aryadanu Dalimunte; Misagi Mukhti Ginting; Reni Ria Armayani Hasibuan (INTERNATIONAL, Journal of Sharia Business Management, 2025)
This study explores the contribution of Micro, Small, and Medium Enterprises (MSMEs) to Indonesia’s economic development by analyzing their role in GDP, employment absorption, regional business distribution, access to financing, and integration into global value chains. Employing a descriptive qualitative approach through literature review, this research utilizes national journals, government reports, and official statistical data. The findings reveal that MSMEs play a significant role in the national economy, contributing 61% to GDP and 97% to employment absorption. However, MSMEs continue to face several challenges, including limited capital, low levels of digitalization, insufficient human resource quality, and infrastructure disparities. Although MSME participation in export activities has increased, further integration into the Global Value Chain (GVC) and utilization of Global E-Commerce (GEC) are required. This study recommends capacity enhancement, digital transformation, expanded access to financing, and the development of a supportive business ecosystem to maximize the contribution of MSMEs to inclusive and sustainable national economic growth.